Website-based Scratch Media Improves Cognitive Learning Outcomes in Science for Junior High School Students: Pengembangan Kecerdasan Sosial Emosional Anak melalui Proyek Penguatan Profil Pelajar Pancasila (P5) di Sekolah Dasar - Maharrani, Berlian Dwi; Wachidah, Kemil (Indonesian Journal of Education Methods Development, 2025)
General Background: The Pancasila student profile is a crucial element designed to foster desired competencies and strengthen students' internal understanding of diversity in the Indonesian education system. Specific Background: The P5 project reinforces the application of this profile throughout the learning process. Knowledge Gap: While P5 is widely implemented, there is a need to understand how these learning activities specifically affect students' social-emotional intelligence. Aims: This research aims to determine the effectiveness of P5 learning activities and their impact on students' social-emotional intelligence. Using a descriptive qualitative method with a phenomenological approach, data were collected through interviews, questionnaires, and documentation. Results: The P5 learning, as delivered by the teacher, was well-executed and aligned with the teaching module. However, the program did not yield results that met the criteria for social-emotional intelligence. Novelty & Implications: This finding highlights a discrepancy between the implementation of P5 and its intended social-emotional outcomes, suggesting that while the program is well-structured, its practical application may not be fully optimized to develop students' social-emotional skills. Highlights : P5 implementation at SDN Candipari 1 was well-executed and aligned with the teaching module. The P5 learning activities did not produce results consistent with the criteria for social-emotional intelligence. The research used a descriptive qualitative method with a phenomenological approach, gathering data through interviews, questionnaires, and documentation. Keywords : Pancasila Student Profile Strengthening Project, Social-Emotional, Elementary School, Qualitative Research, Student Competency